The Impact Of The Arabic Language Curriculum For Malay-Speakers And Qur'anic Words In The Development Of Language And Literary Skills - Mahmoud Ibrahim; El Sayed Mohamed Salem; Mohamed Salah El-Din Ahmed Fath El-Bab; Abdullah Ramadan Khalaf Morsi; Amal Mahmoud Ali Ibrahim; Nurazan Mohmad Rouyan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The link between the Qur'an and the Arabic language is an eternal bond, so this research, which provides a proposed model for building a curriculum to teach the Arabic language to Malay-Speaker using the vocabulary common to Malay and Qur'anic words, was hoped to have the greatest impact in facilitating students' linguistic and literary skills for Malay-speakers. The problem of the study: What prompted the researchers to do this research are two reasons, the first reason is the scarcity of curricula and books that teach the Arabic language that depends on the employment of the Holy Quran, mainly in its construction, and the second is the scarcity of curricula and books teaching the Arabic language that adopt the common words between the Malay language and the Qur'anic words, and therefore this study was interested in shedding light on the importance of employing the common vocabulary between the Malay language and the Qur'anic words and benefiting from them in building a curriculum to teach Arabic to Malay-Speakers. Researchers relied on a descriptive and analytical approach in preparing their research. One of the objectives of the study is to outline an integrated educational curriculum, using the common vocabulary between Malay language and Qur'anic words, to develop the linguistic and literary skills of Malay Speakers, The other objective is to introduce the importance of using the common vocabulary between Malay language and Qur'anic words in building a curriculum to teach the Arabic language to Malay-Speakers, and to demonstrate the impact of that curriculum on the development of language and literary skills. The results of this study showed that the use of common vocabulary between Malay language and Qur'anic words in building a curriculum to teach the Arabic language to Malay-Speakers, has the greatest impact on the development of linguistic and literary skills of Malay-speaking students, as well as the curriculum has a great impact in facilitating the task of the teachers of Arabic language for Malay-Speakers. Researchers hope this research should contribute to the benefit of students seeking to learn Arabic from Malay Speakers, as well as Arabic language teachers, researchers, and those interested in the field of teaching Arabic to Malay Speakers.